Conceptualization of chemical kinetics using a visually enhanced teaching technique; a developed MS Excel worksheet/system - et. al., L.S.L.K. Fernando, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Chemical kinetics or reaction kinetics is renowned as a division of physical chemistry which includes with understanding the rates of chemical reactions. As physical chemistry lessons play a vital role in secondary level chemistry syllabus in Sri Lanka, in order to understand the concepts of chemical kinetics the use of only traditional chalk and board method is inadequate. Accordingly, this study was carried out with the objectives of developing a suitable teaching aid using MS Excel and visual basic to conceptualize the theories in chemical kinetics enabling to promote the insight while upgrading the standard of chemistry education by combining it with visually enhanced teaching. Thirty students with similar knowledge level were randomly divided into two groups and same chemistry lessons were conducted leaving only one difference in their instructional method; the MS Excel worksheet was used along with the traditional chalk and board for one group while only the traditional chalk and board method was used for the other group. Same question paper was given for both groups at the end. The student’s t test was used as the analytical tool to analyze the results. The statistical results confirmed that the used system supported the students to visualize and understand the concepts related to chemical kinetics in a better manner. For this sample, at 95% confidence level t calculated (10.372) is greater than t tabulated (2.048) suggesting that this proposed teaching aid improved the students’ knowledge and understanding significantly than that of the ordinary chalk and board method. This developed MS Excel worksheet/system together with its findings will be beneficial to several sectors such as chemistry students, teachers, school administrators and policy makers..